Family Care, Economic Stress, and Depressive Symptoms Among Chinese Adults During the COVID-19 Outbreak: Difference by Urban and Rural Areas - Liu, Chengbin; Zhang, Liyuan; Ahmed, Farooq; Shahid, Muhammad; Wang, Xiaohua; Wang, Yiqing; Wang, Junlan; Guo, Jing (Frontiers in Psychiatry, 2021)
Abstract Background: Although several studies have shown an association of family care with a high level of depressive symptoms, the relationship between them remains indistinguishable. Objective: This study aims to examine the associations between family care, economic stress, and depressive symptoms among Chinese adults in urban and rural areas during the COVID-19 outbreak. Methods: Based on cross-sectional data collected through online surveys from February 1st to 10th 2020 in China the present study recruited 2858 adults. It used multiple linear regression to examine the association between family care and depressive symptoms, while economic stress was examined as moderators on the above relationship. Results: The results showed that caring for both the elderly and children was significantly associated with higher depressive symptoms (B=2.584, 95%CI:1.254,3.915). Also, caring for the elderly only was also associated with higher levels of depressive symptoms among rural caregivers (B=3.135, 95%CI: 0.745,5.525) . Meeting the care needs was significantly associated with lower depressive symptoms, while for rural caregivers, the results were not significant. Besides, economic stress strengthened the effect of family care needs on depressive symptoms for sandwich-generation caregivers who provide care to the elderly and children (B=0.605, 95%CI:0.077,1.134). While in rural areas, the moderation effects of economic stress were only found for elderly caregivers(B=1.106, 95%CI: 0.178,2.035). Conclusion: These findings suggest that we should pay more attention to the family caregiver’s mental health, especially for sandwich-generation caregivers and their economic stress. Moreover, additional measures are needed to reduce inequities in access to health care and social security between urban and rural areas. Keywords: Family care; Depressive symptoms; COVID-19; Economic stress; Urban-rural difference